Correlation between the Arbitrators’ Discretion and the Natural Justice in Arbitration Proceedings - N. A. Kapustina (Московский журнал международного права, 2024)
INTRODUCTION. This article discusses the approaches developed by the courts of the Asia-Pacific region (on the example of Singapore, Hong Kong and Malaysia) on the relationship between the arbitrators’ discretion when considering disputes and the observance of the principle of natural justice.The purpose of the article was to analyze the approaches of national courts to the interpretation of the principle of natural justice in the context of the implementation by arbitration of its discretionary powers in resolving disputes submitted to them. The risk that the arbitrators fail to find a balance between discretionary powers and natural justice is that the award may be set aside.MATERIALS AND METHODS. The study was based on the analysis of national legislation of the countries of the Asia-Pacific region, the practice of arbitration centers and judicial bodies, as well as the existing positions of researchers specialized in the natural justice issues and practitioners in the field of international commercial arbitration. The methodological basis of the research includes general scientific (analysis) and special legal (comparative legal) methods.RESEARCH RESULTS. International commercial arbitration is widely regarded as an alternative dispute resolution mechanism to litigation in national courts. However, national courts are often involved in reviewing arbitral awards in the context of their setting aside in order to ensure that the arbitral procedure complies with the fundamental principles of natural justice. The understanding of the principle of natural justice is not the same in all jurisdictions and depends on the venue of the arbitration, as well as on what rules the parties have agreed to govern the proceedings. Arbitral discretion is important in filling the gaps left by the rules and guidelines formulated by various arbitral institutions and practices.DISCUSSION AND CONCLUSIONS. The author considers the approaches of the courts of Singapore, Hong Kong and Malaysia ensuring a balance between arbitrators ‘discretion and compliance with the principle of natural justice, and also, based on the analyzed practice, suggests ways to minimize the risk of annulment of an arbitral award due to a violation of natural justice, namely the need for an established procedural protocol, which would provide certainty and eliminate problems arising in connection with the application of discretion by arbitration.